Ta’dib (Penanaman Adab) di Pondok Pesantren - Kholil, Munawar; Rahman, Abdur; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2024)
Etiquette (adab) must be a primary focus for students (santri) in modern pesantren (Islamic boarding schools), especially for those studying religious knowledge. The aim of learning adab is to ensure that the knowledge gained is beneficial and blessed, as a small amount of knowledge accompanied by adab is better than a large amount of knowledge devoid of adab. The role of pesantren is vital in the cultivation of adab (ta'dib) among its students. The methods of instilling adab include: 1) Teaching methods, which encompass classroom learning and the study of religious texts (ta'lim kitab). 2) Mentorship methods, which include: role modeling, advice and motivation, training and habituation, discipline, rewards, and punishments. Therefore, pesantren are expected to produce competent and ethical Islamic leaders.